RESPON BERBAGAI GENOTIPE JAGUNG UMUR GENJAH PADA BERBAGAI JARAK TANAM - St. Subaedah; Sudirman Numba; Saida Saida; Andi Ralle (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2018)
This study aims to analyze the response of various genotypes of early maturity at various plant spacing. The study was conducted from May to July 2017.The study was designed following a split-plot design pattern.As the main plot is the genotype of maize consisting of four genotypes G1, G2, G3, and G4.As a subplot is a spacing arrangement consisting of three levelnamely: sapacing of 70 cm x 20 cm (J1), spacing of 60 cm x 20 cm (J2) and spacing of 50 cm x 20 cm (J3).The results showed that the growth and production of maize was affected by the genotype and spacing used. The maize genotypes G3 and G4 resulted in higher plants with a closer spacing (60 x 20 cm and 50 x 20 cm) than with wider plant spacing (70 x 20 cm). In planting distance treatment showed that plant spacing of 60 x 20 cm and 50 x 20 obtained significantly higher production that is between 8.95 to 9.35 t / ha compared with the spacing of 70 x 20 cm which produces only 7.64 t /Ha.